ما يحتاجه معلّم التّجويد من علمي النّحو والصّرف - سليماني, محمد; ضمايدة, مختار (My University, 2022)
"موضوع البحث كان بعنوان ""ما يحتاجه معلّم التّجويد من علمي النَّحْوِ والصّرف""، ولا يخفي على ذي لبّ ما لعلمي النَّحو والصَّرف من علاقة وطيدة لا تنفكّ بحال عن كتاب الله عز وجل؛ وذلك يطرح الإشكالية الآتية: ماهي أهم المسائل النّحويّة والصّرفيّة الّتي يحتاجها معلّم التّجويد أثناء أداء مهمّته؟ وكيف يستفيد منها في جانب التّدريس لعلم التّجويد؟ حتى يبلّغ رسالته كاملة دون غلط. ولمعالجة هذا الإشكال سلكنا الخطّة الآتية: المبحث الاوّل: ما يحتاجه معلم التّجويد من نحو وصرف في بابي ميم الجمع وهاء الضّميير، وتحته مطلبان، والمبحث الثاني: ما يحتاجه معلّم التّجويد من نحو وصرف في بابي الممدود والمقصور، وتحته أربعة مطالب، والمبحث الثالث: ما يحتاجه معلّم التّجويد في باب الهمز، وتحته أربعة مطالب أيضا، والمبحث الرّابع: ما يحتاجه معلّم التّجويد في بابي الفتح والإمالة، وتحته أربعة مطالب كذلك، والمبحث الخامس: ما يحتاجه معلّم التّجويد في بابي ياءات الإضافة و ياءات الزّوائد، وتحته ثلاثة مطالب، والمبحث السّادس: ما يحتاجه في معرفة الوقوف على أواخر الكلم، وتحته مطلبان. وتوصّلنا في الأخير إلى أنّ: - جميع مسائل التّجويد مستفادة من علوم اللّغة، وعلى رأسها علما النّحو والصّرف. - مباحث التّجويد جلّها أو أغلبها صرفيّة، وإن كان بينهما فرق وهو أنّ علم التّجويد يعنى بالجانب الصّوتي، فيما يعنى علم التّصريف بجانب البناء. مما يحتِّم على مَنْ أراد أن يضبط التَّجويد تدريسا وتعلُّمًا وتعليمًا فلا بدَّ له من دراية بعلم النّحو والصّرف.""Research Summary The topic of this research was an important subject, because it is related to the teacher of Tajweed and Qur’an; That is, what the teacher of Tajweed knowledge requirements for grammar and morphology, and it is not hidden for those who has mind that the grammar and morphology sciences have a close relationship that does not break away in any case from the Qur’an. Why not, and they are the judge for the Arabic tongue which chosen by Allah to be a tongue of his last Book down on his best creations and his last prophet and messenger, Muhammad, may God’s prayers and peace be upon him. Therefore, it is necessary for those who wants to teach the words of the Qur’an, their control and their Tajweed, to come back for what is used to control the Arabic tongue, in terms of grammar and morphology. From based on this relationship and importance between the sciences of grammar and morphology and the science of Tajweed, this research we have done this research, and we mentioned on that what a teacher of Tajweed needs from the sciences of grammar and morphology. In The chapter on the plural Meem and the pronoun Ha’, and what it needs in the chapter on the extended and shortened nouns, the chapter on the pronouns, the opening and the inclination, the Ya’s of additions, the Ya’s of addition, the stopping and the beginning, and some exceptions under each chapter. We have tried by these chapters to explain how The Tajweed teacher benefits from it grammatically and morphologically. So we conclude the fact that says; most of Tajweed science issues and researches based on grammar and morphology sciences. For that; whoever wants to master Tajweed whether teaching, learning or educating, he must have knowledge of them. Allah bless. "م\
مذكرة ماستر
Keywords: التجويد، النحو، الصرف; intonation, grammar, morphology